2006
DOI: 10.1111/j.1365-294x.2006.02969.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombination and selection shape the molecular diversity pattern of nitrogen‐fixing Sinorhizobium sp. associated to Medicago

Abstract: We investigate the genetic structure and molecular selection pattern of a sympatric population of Sinorhizobium meliloti and Sinorhizobium medicae. These bacteria fix nitrogen in association with plants of the genus Medicago. A set of 116 isolates were obtained from a soil sample, from root nodules of three groups of plants representing among-species, within-species and intraline diversity in the Medicago genus. Bacteria were characterized by sequencing at seven loci evenly distributed along the genome of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
89
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 74 publications
7
89
0
Order By: Relevance
“…Based on sequencing of several loci, S. medicae is less diverse than S. meliloti, especially at chromosomal loci (Bailly et al, 2006;van Berkum et al, 2006). Indications of directional and balancing selection have been identified for the nod gene region on pSMED02/pSymA and the region involved in polysaccharide synthesis on pSMED01/pSymB, respectively, in sympatric populations of S. meliloti and S. medicae (Bailly et al, 2006). Such diversity patterns suggest that recombination has an important role in shaping the diversity of both species.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on sequencing of several loci, S. medicae is less diverse than S. meliloti, especially at chromosomal loci (Bailly et al, 2006;van Berkum et al, 2006). Indications of directional and balancing selection have been identified for the nod gene region on pSMED02/pSymA and the region involved in polysaccharide synthesis on pSMED01/pSymB, respectively, in sympatric populations of S. meliloti and S. medicae (Bailly et al, 2006). Such diversity patterns suggest that recombination has an important role in shaping the diversity of both species.…”
Section: Introductionmentioning
confidence: 97%
“…Although S. meliloti 1021 does not have any comparable plasmid, additional plasmids have also been observed in some other strains of this species Olivares, 1993, 1994;Stiens et al, 2006Stiens et al, , 2007Kuhn et al, 2008). Based on sequencing of several loci, S. medicae is less diverse than S. meliloti, especially at chromosomal loci (Bailly et al, 2006;van Berkum et al, 2006). Indications of directional and balancing selection have been identified for the nod gene region on pSMED02/pSymA and the region involved in polysaccharide synthesis on pSMED01/pSymB, respectively, in sympatric populations of S. meliloti and S. medicae (Bailly et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ad hoc Committee for the Re-evaluation of the Species Definition in Bacteriology (Stackebrandt et al, 2002;Gevers et al, 2005) suggested the sequence analysis of a set of protein-encoding genes as alternative phylogenetic markers, or multilocus sequence analysis (MLSA). Several recent studies have confirmed that sequences from housekeeping genes can be used for identification at the species level (Wertz et al, 2003;Zeigler, 2003), for evolutionary population genetics and in taxonomy (Stepkowski et al, 2003;Vinuesa et al, 2005a,b;Bailly et al, 2006). The analysis of a small number of carefully selected gene sequences may equal or even surpass the precision of DNA-DNA hybridization for the quantification of genome relatedness and this approach thus has the potential to replace cumbersome DNA-DNA hybridizations (Zeigler, 2003, Martens et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…'Ensifer mexicanus' and 'Sinorhizobium chiapanecum' were described using phenotypic analysis, phylogenies of the recA, gyrA, nolR, rpoB, rrs and symbiotic genes and confidence intervals of sequence similarity to estimate both inter-and intraspecies variation; all were in correlation with DNA-DNA hybridization data (Lloret et al, 2007;Rincó nRosales et al, 2009). In addition, MLSA has been applied in diversity studies of the genera Enterococcus, Aeromonas and Ensifer (Sinorhizobium) (Naser et al, 2005;Soler et al, 2004;Bailly et al, 2006) and it has been reported as being a highly reproducible and economical method for rapid and reliable species identification.…”
Section: Introductionmentioning
confidence: 99%